Representation of Public Library Recreation Function in the film The Library (2015) - Silmi Morita; Laksmi Laksmi (Pustabiblia: Journal of Library and Information Science, 2018)
This thesis analyses the representation of recreation function in the film The Library (2015). This 20-minute film tells of a teenage girl who gets happiness in the library and gets a lesson about the power of love. The background of all scenes in this film are in a public library in Britain and Emily’s school. This research is using semiotic method with syntagmatic-paradigmatic relation analysis by Roland Barthes. The unit of analysis is the storyline, characters, sentences or statements in each scene in the film. The result of syntagmatic analysis shows that representation of recreation function has worked well as seen from how Emily voluntarily visited library every day to read collections which made her feel love. Paradigmatic analysis shows that the background of the library is the main element that influences the feelings of the characters, such as happiness and pleasure. The conclusion is that this film contains representation of recreation function described with expressions and gestures of Emily and other characters in this film which shows that she was happy after reading the collections in this library and felt new experience that brought her happiness and how Ruth and John found their love. Inaddition, this film conveys education that anyone has the same rights when they visit public library. Indirectly, this film persuasively invites audience to visit public library because they can obtain not only knowledge but also can use its library collection for entertainment and valuable experience.